Intraperitoneal adipose tissue is strongly related to survival rate in a mouse cecal ligation and puncture model. Issue 2 (12th February 2016) - Niiyama, Shuhei; Takasu, Osamu; Sakamoto, Teruo; Ushijima, Kazuo
Abstract : Cecal ligation and puncture (CLP) models exhibiting polymicrobial sepsis are considered as the gold standard in sepsis research. However, despite meticulous research being conducted in this field, only few treatment drugs are available, indicating that CLP sepsis models do not completely mimic human sepsis models. The greatest flaw in CLP models is abscess formation because the localization of inflammation caused by abscess formation increases the survival rate. Therefore, by resecting intraperitoneal adipose tissue, we developed a mouse CLP model wherein abscess formation was unlikely. Survival rates at 7 days postoperatively were compared using the Kaplan–Meier method for an intraperitoneal adipose tissue resection group (resection group, n =34), an intraperitoneal adipose tissue non‐resection group (non‐resection group, n =35) and a sham group ( n =10). Results indicated that the survival rate was significantly higher in the non‐resection group compared with the resection group. Intraperitoneal macroscopic findings in the non‐resection group revealed the localization of inflammation caused by abscesses formation covered in adipose tissue. The survival rate for the sham group was 100%. Measurement of interleukin 6 (IL‐6) indicated that during the 12 h after the creation of the CLP model, the median level of IL‐6 was 1300 (552–3000) pg ml −1 in the non‐resection group ( n =19) and 3000 (1224–8595) pg ml −1 in the resection group ( n =19). Meanwhile, for the sham group, IL‐6 values were below measurement sensitivity in most cases (9/10 mice). Thus our results suggest that, in CLP models, intraperitoneal adipose tissue has an important role in abscess formation and is strongly related to the survival rate. Inflammation: A better model of sepsis: The surgical removal of fat deposits in mice results in a more realistic animal model of the sepsis resulting from severe infection. For decades, researchers have studied this potentially fatal inflammatory process by introducing punctures into the mouse intestinal wall. The usefulness of this model can be undermined if abscesses form to physically confine the immune response that drives sepsis, but Shuhei Niiyama and colleagues at Japan's Kurume University School of Medicine have devised a potential solution. They determined that pockets of fatty tissue around the intestine contribute to abscess formation, and that removing these deposits considerably promotes the onset of sepsis after intestinal puncture. These results support prior evidence that fat cells can generate signals that restrain inflammation, and could lead to more effective studies of drugs for treating this toxic outcome of infection.